Digital Safety Education for the Constituents of West Nusa Tenggara Electoral District 2 - Surbakti, Feliks Prasepta Sejahtera (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to provide the public with practical knowledge and skills in cybersecurity, focusing on securing digital devices, digital identities, and managing digital footprints. The method used involved interactive seminar-based training and case simulations. Participants were trained to understand various types of cyber threats, recognize digital scams, and implement security measures such as using strong passwords, two-factor authentication, full encryption, and antivirus software. Additionally, participants were encouraged to manage their digital footprints responsibly to minimize the risk of privacy violations. To evaluate the effectiveness of the program, a structured instrument in the form of pre-test and post-test questionnaires was used. The instrument measured participants’ understanding of key cybersecurity concepts and safe digital practices. The data collected were analyzed using descriptive statistics, specifically by comparing the average scores before and after the training to determine the extent of knowledge improvement. The results of this program showed a significant improvement of 35% in participants’ awareness and understanding of digital security. In conclusion, this program successfully enhanced participants’ digital literacy in cybersecurity and contributed to building a safer digital ecosystem in Indonesia.